Analytical methods involving separation techniques for determination of low-molecular-weight biothiols in human plasma and blood - Isokawa, Muneki; Kanamori, Takahiro; Funatsu, Takashi; Tsunoda, Makoto (Journal of chromatography. B, Analytical technologies in the biomedical and life sciences, 2014)
•Biothiols play important roles in biological processes.•Thiol concentrations in human plasma and blood are related to diseases.•We review analytical methods for biothiols applied to human plasma and blood. Low-molecular-weight biothiols such as homocysteine, cysteine, and glutathione are metabolites of the sulfur cycle and play important roles in biological processes such as the antioxidant defense network, methionine cycle, and protein synthesis. Thiol concentrations in human plasma and blood are related to diseases such as cardiovascular disease, neurodegenerative disease, and cancer. The concentrations of homocysteine, cysteine, and glutathione in plasma samples from healthy human subjects are approximately in the range of 5–15, 200–300, and 1–5μM, respectively. Glutathione concentration in the whole blood is in the millimolar range. Measurement of biothiol levels in plasma and blood is thought to be important for understanding the physiological roles and biomarkers for certain diseases. This review summarizes the relationship of biothiols with certain disease as well as pre-analytical treatment and analytical methods for determination of biothiols in human plasma and blood by using high-performance liquid chromatography and capillary electrophoresis coupled with ultraviolet, fluorescence, or chemiluminescence detection; or mass spectrometry.